Transformasi Digital UMKM Cemilan Atos-Atos melalui Rancang Bangun Sistem E-Commerce Berbasis Website - Wulandari, Ika Arthalia; Ramadhan, Mohammad Bintang; Ridwan, Muhammad; Gara, Muhammad Hakam (Universitas Muhammadiyah Metro, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a significant contribution to Indonesia's economic growth, particularly in employment. However, many MSMEs have not yet optimally utilized information technology in their business processes. One such business is the Atos-Atos Snacks MSME, which still conducts sales activities conventionally and is limited to its surrounding area. Despite its strategic location, the product sales system is still carried out manually, and the service process is also conventional, without the support of digital devices such as computers or laptops. The payment method is cash directly on site or through an order delivery system to consumers, which is less efficient in terms of time, but also limits the potential for market expansion and increasing sales volume. This study aims to implement e-commerce to simplify the buying and selling process, allowing sellers and buyers located in different locations to conduct transactions online. The system development method used is the System Development Life Cycle (SDLC) with a waterfall approach, starting from requirements analysis, system design, implementation, and testing. The system was built using the PHP programming language with the CodeIgniter4 framework and MySQL as the database, and it applies the Model-View-Controller (MVC) architecture to separate business logic, display, and data processing. System testing was conducted using the Black Box Testing method to verify system functionality, as well as direct validation by the MSME owner as the end user. The test results showed that the system can run according to user requirements and help speed up the transaction process and expand product marketing reach. With the implementation of this system, it is hoped that the Atos-Atos Snacks MSME can improve operational efficiency and competitiveness in the digital era.